Bench‐Stable N‐Heterocyclic Carbene Nickel Precatalysts for C−C and C−N Bond‐Forming Reactions. Issue 13 (2nd May 2018) - Strieth‐Kalthoff, Felix; Longstreet, Ashley R.; Weber, Jessica M.; Jamison, Timothy F.
Abstract: Herein, we introduce a new class of bench‐stable N ‐heterocyclic carbene (NHC) nickel‐precatalysts for homogeneous nickel‐catalysis. The nickel(II) complexes are readily activated to Ni 0 in situ under mild conditions, via a proposed Heck‐type mechanism. The precatalysts are shown to facilitate carbonyl‐ene, hydroalkenylation, and amination reactions. Abstract : NHC Nickel Precatalysts : Bench‐stable N ‐heterocyclic carbene (NHC) nickel(II) precatalysts have been designed to undergo a Heck‐like mode of activation under mild conditions. Catalytic efficiency is demonstrated with carbonyl‐ene, hydroalkenylation, and amination reactions.